2017
DOI: 10.1115/1.4038280
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of External Casing Impingement Cooling Manifold Standoff Distance on Casing Contraction for Thermal Control of Blade Tip Clearance

Abstract: Thermal closure of the engine casing is widely used to minimize undesirable blade tip leakage flows thus improving jet engine performance. This may be achieved using an impingement cooling scheme on the external casing wall, provided by manifolds attached to the outside of the engine. The assembly tolerance of these components leads to variation in the standoff distance between the manifold and the casing, and its effects on casing contraction must be understood to allow build tolerance to be specified. For co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…By note to the previous studies, it can be clearly found that the blade tip clearance has a significant effect on the performance of the turbine and its variation may worsen engine performance and reduce the components' life span. To overcome these issue, some control methods have been presented especially active and passive thermal [19][20][21], active mechanical [22], passive and active pneumatic systems. However, desire to control the clearance actively must be balanced against the dangers of introducing unreliable systems into the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…By note to the previous studies, it can be clearly found that the blade tip clearance has a significant effect on the performance of the turbine and its variation may worsen engine performance and reduce the components' life span. To overcome these issue, some control methods have been presented especially active and passive thermal [19][20][21], active mechanical [22], passive and active pneumatic systems. However, desire to control the clearance actively must be balanced against the dangers of introducing unreliable systems into the turbine.…”
Section: Introductionmentioning
confidence: 99%